Evidence for different nutrient partitioning in Boran (Bos indicus) and Boran x Holstein cows when re-allocated from low to high or from high to low feeding level - Jenet, A.; Fernández Rivera, S.; Tegegne, Azage; Wettstein, H.R.; Senn, M.; Saurer, M.; Langhans, W.; Kreuzer, M. (Wiley, 2006)
This study tested the hypothesis that purebred Boran (Bos indicus) cows and crossbreds of Boran and Holstein respond differently to long-term changes of feeding level in nutrient partitioning to milk and body fat stores. A total of 27 cows of these two genotypes were subjected either to a low or a high feeding level from their first oestrus as heifers until birth of their third calf. Half of the cows of each genotype were then switched to the other feeding level during the third reproduction cycle. If at all, Boran cows responded to a change in the feeding level almost exclusively by a corresponding change in body weight but not milk yield. Crossbred cows kept continuously on the low feeding level had a lower milk yield than those continuously fed the high level, but lost similar amounts of body weight. In crossbred cows, changing the feeding level from high to low was accompanied by a mobilization of body reserves, whereas a change from low to high level resulted mostly in an increase in milk yield. Certain other genotype differences in metabolic response were obvious from differences in body composition and from the metabolic profile either reflected in blood (particularly insulin-like growth factor I) or in adipose tissue (lipoprotein lipase). Reproductive performance differed between genotypes, with shorter lactations associated with earlier occurrences of the first oestrus in the Boran cows. Generally, feeding history appeared to have at least as much influence on energy partitioning as the actual feeding level. In conclusion, purebred Boran cows seem to react to long-term food fluctuations mainly by mobilizing and restoring body fat reserves, whereas cows crossbred with Holstein tend to spend extra energy preferentially for milk production